The Relationship between Emotional and Spiritual Intelligence and the Attitude of Students toward Extramarital Relations - Shirin Haji-Adineh; Maryam Kalhornia-Golkar (Shahid Beheshti University of Medical Sciences, 2019)
Background and Objective: One of main factors threatening family commitments is extramarital relations. Therefore, the objective of this study was to examine the relationship and role of emotional and spiritual intelligence in predicting the attitude of students toward extramarital relations. Materials and Methods: The study was of descriptive-correlational design. The statistical population of the study included all master students of Islamic Azad University North Tehran Branch during the academic year 2017-2018. From this population, 351 students were selected using multistep cluster sampling method. Data were collected via Emotional Intelligence Questionnaire, Spiritual Intelligence Questionnaire and the Questionnaire for Attitudes toward Extramarital Relations and analyzed with Pearson correlation coefficient and stepwise regression analysis by SPSS-25. Results: The mean (SD) age of students was 27.6 (4.8). Increased emotional intelligence score with mean (SD) 215.7 (19.2) and the spiritual intelligence score with mean (SD) 57.7 (6.8), correlated with decreased score of attitude toward extramarital relations with mean (SD) 28.8 (4.1). The results of stepwise regression analysis indicated that in the first step, spiritual intelligence could solely explain 4% of the changes in the attitudes score toward extramarital relations, which increased to 6% in the second step with the introduction of the emotional intelligence as predicting variable. Therefore, spiritual intelligence was the strongest predictor variable in reducing the score of the attitudes toward extramarital relations students. Conclusion: The study showed that the higher the emotional and spiritual intelligence, the less carefree are the attitudes towards extramarital relations, and that spiritual intelligence was the strongest predictor for reducing the score of attitudes towards extramarital relations among students. DOI: http://doi.org/10.22037/ch.v6i4.23331